The interrelationship between sleep disturbance symptoms and aggression before and after the campus closure of the COVID-19 pandemic: insight from a cross-lagged panel network model - Zou, Jinhua; Bian, Baohua; Li, Min; Liu, Gang (Frontiers in Public Health, 2024)
The pandemic of COVID-19 is detrimental to sleep quality and increases aggression among college students. Nevertheless, relevant studies were rare. Hence, we collected longitudinal data during and post-campus closure in the current study to investigate the relationship between sleep disturbance and aggression.Data from 665 college students (59.2% females, Mean age = 19.01, SD age = 1.25) were collected before (wave 1) and after (wave 2) the campus closure of COVID-19.All participants were asked to fill in the Buss-Perry Aggression Questionnaire and Youth Self-rating Insomnia Scale. Two symptom networks and a cross-lagged panel network are formed and tested.Hostility has the highest centrality in the symptom network both in wave 1 and wave 2 and bridged sleep disturbance and aggression. "easily be woken" -"wake up too early" and "wake up with tired" -"function hindrance" are two important symptom association in networks of wave 1 and wave 2. All symptoms except "difficulty in falling asleep" and "easily be woken" ameliorated after closure. Moreover, "physical aggression" and "hostility" can trigger other symptoms in wave 2.As the first study about aggression and sleep disturbance in the background of COVID-19, we provide valuable information about the relationship between sleep disturbance and aggression on symptom dimension.